Anxiety and coping strategies of adolescents with chronic diseases (a study of adolescents in remission from oncological diseases) - N. V. Shilovskaya (Military Medicine, 2026)
T h is ar ticle presents the results of a study on anxiety and coping behavior in adolescents who have achieved remission from oncological diseases (n = 13). The study examines these phenomena in the context of age (early and late adolescence) and gender. A multi-method approach was employed, integrating phenomenological interviews to describe the structure of the participants’ experiences, psychodiagnostic techniques, and physiological measurements using a «Reacor» biofeedback device to record galvanic skin response (GSR) and photoplethysmography (PPG). The findings confirm the existence of significant gender and age-related differences in the experience of anxiety and the utilization of coping strategies. These results can serve as a foundation for developing effective support and intervention programs aimed at managing anxiety in adolescents.